2016
DOI: 10.1002/dta.2005
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive avidin‐biotin ELISA for detection of nandrolone and testosterone in dietary supplements

Abstract: Avidin-biotin technology was used for the implementation of an enzyme-linked immunosorbent assay (AB-ELISA) as a sensitive method for the detection of anabolic androgenic steroids (AAS) present in dietary supplements. Using click chemistry, novel haptens (linker-optimized biotinylated nandrolone (NT) and testosterone (T) at positions C-3 and C-17, respectively) were designed and synthesized to be then applied as four different immobilized competitors in a proposed set of four indirect competitive AB-ELISAs. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
(82 reference statements)
0
6
0
1
Order By: Relevance
“…However, only a few articles have reported click chemistry being used in immunoassay. 41,46 This study demonstrated how to construct effective conjugates based on a unique click chemistry for improvement of sensitivity in immunoassay, which would widen the application of click chemistry in immunoassay. As shown in Table 1, IC 50 values obtained from the two heterologous coating antigens, G1−conalbumin (CON) (0.71 μg/mL) and G2−OVA (0.06 μg/mL), were much lower than those from the homologous coating antigen GCA−OVA (5.08 μg/mL).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…However, only a few articles have reported click chemistry being used in immunoassay. 41,46 This study demonstrated how to construct effective conjugates based on a unique click chemistry for improvement of sensitivity in immunoassay, which would widen the application of click chemistry in immunoassay. As shown in Table 1, IC 50 values obtained from the two heterologous coating antigens, G1−conalbumin (CON) (0.71 μg/mL) and G2−OVA (0.06 μg/mL), were much lower than those from the homologous coating antigen GCA−OVA (5.08 μg/mL).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Praktické provedení LFIA je podobné těhotenskému testu na hCG. Vyvinutou metodou ELISA lze prokázat anabolické steroidy už v koncentracích řádu jednotek až desítek pg/ml a citlivost LFIA metod při jednoduchém vizuálním vyhodnocení je v řádu jednotek ng/ml, což pro potřeby screenin gu plně postačuje [9]. Metody jsou schopny dete kovat široké spektrum anabolických steroidů v jed nom testu.…”
Section: Laboratorní Průkaz Anabolikunclassified
“…17 to it, biotinylated antibodies can also be applied. 19 By converting the antigen−antibody interaction to avidin−biotin interaction, the specific binding is greatly enhanced, thus improving the sensitivity and specificity. However, these two methods involve the change of the structures of antibodies and may further influence the binding reactivity.…”
Section: ■ Introductionmentioning
confidence: 99%